G300 Perinatal arterial ischaemic stroke – a multi-level collaborative retrospective regional study. (12th March 2018) - Foulkes, S; Wong, MC; Gallagher, K; Austin, T; Chitre, M
Abstract : Aims: Perinatal arterial ischaemic stroke (PAIS) presents in the neonatal period or later ('presumed'cases) and is a leading cause of hemiplegic cerebral palsy. Accurate estimation of the incidence and disease burden is challenging and studies of presumed cases are few. Our region covers 5 counties and has a population of approximately 5 million. We aim to review the regional clinical and radiological characteristics of children with PAIS through collaboration between one tertiary neonatal centre and an epilepsy network. The preliminary data is presented. Methods: Term neonates diagnosed with acute PAIS presenting to the tertiary neonatal unit in 2014 and 2015 were identified through electronic patient record (Badgernet) and a local database. Presumed PAIS cases presenting to the tertiary paediatric neurology unit between 2011–2015 were identified though clinical coding. Members of an established regional epilepsy network consisting of community, secondary, and tertiary paediatric clinicians were invited to identify local presumed PAIS cases over the same time period. Retrospective data was collected through medical records. Results have been received from 6 units to date and data collection is ongoing. Results: Neonatal cases all presented with seizures. While the majority (78%) of presumed cases presented with pathological handedness, there is a male (60%) and left sided infarct (62.5%) predominance. 21% of infants with presumed PAIS cases had neonatal symptoms. These included changes in muscle tone (60%), level of alertness (20%) and feeding problems (40%). Amongst all PAIS cases there was a significant burden of language (31%), visual (21%), behavioural (10%) and learning impairment (26%) in addition to the recognised movement difficulties and seizures. Conclusion: The clinical characteristics of PAIS in our region are similar to the published literature. Clinicians should have a high index of suspicion in neonatal cases of unexplained changes in muscle tone, respiratory or feeding difficulties which may lead to earlier diagnosis and intervention. Ongoing studies using a network approach would allow presentation of the wider spectrum of PAIS, producing more representative clinical data.